Disinformation in Political Advertising in the Context of First-Time Voters’ Advertising Literacy - Ľudmila Čábyová; Denis Javořík (Communication Today, 2025)
The authors of this research study investigated the ability of first-time voters to comprehend, identify and evaluate political advertising along with their ability to understand and identify disinformation in political advertising. Two groups were compared: one that received media education as a compulsory subject in school and one that did not. This study also showcases the positive impact of media education on first-time voters, since it revealed a significant difference in advertising literacy levels between these groups. The results of the study show that there were notable improvements in defining and identifying political advertising and disinformation among media-educated students. Both groups of students were able to define the goals of disinformation in political advertising and most consider them unethical. The highest score in both groups was achieved in verifying media sources and news. This study highlights the paramount importance of advertising literacy for first-time voters since it gives them the tools to discern political advertising and enables them to make well-informed decisions during the electoral process. It also emphasises the importance of media education.